Attitudes toward female circumcision among Somali immigrants in Oslo: a qualitative study - Gele AA; Kumar B; Hjelde KH; Sundby J (Dove Medical Press, 2012)
Abdi A Gele1,2, Bernadette Kumar3, Karin Harsløf Hjelde3, Johanne Sundby21The Department of Social Science, Oslo University College, 2Section for International Health, Department of General Practice and Community Medicine, University of Oslo, 3Norwegian Center for Minority Health Research, Oslo, NorwayAbstract: Due to its negative impact on public health, female circumcision (FC) has gained increased attention from international communities and the Norwegian public in recent decades. In 1995, the Norwegian government outlawed the practice and simultaneously developed a package of measures aimed at preventing and ultimately eradicating FC in Norway. Like many other Western countries, immigrants of Somali descent constitute the largest immigrant group in Norway from countries with FC traditions. Although this immigrant group is often perceived as a cultural society that supports FC generally as a practice, there appears to be a lack of studies that explore the impact of acculturation and the Western social context on Somali immigrants’ attitudes toward the practice. Against this background, this paper explores the attitudes of Somalis living in Oslo, Norway to the practice of FC. Findings from this qualitative study indicate that Somalis in Oslo have, to a large extent, changed their attitude toward the practice. This was proven by the presence in Oslo of a large number of Somali parents who left their daughters uncut as well as Somali girls, boys, men, and women who attribute being uncircumcised a high status. This study adds to the knowledge of the process of abandonment of FC among immigrants in the Western countries. The study highlights the success that has been achieved in improving attitudes toward the practice of the Somali community in Oslo, Norway, as well as emerging challenges that need to be addressed further.Keywords: female circumcision, attitude, behavior, immigrants, Somalis